Wednesday

April 16, 2014

April 16, 2014

Posted by **Ash** on Monday, July 25, 2011 at 7:08pm.

- college algebra -
**Julie**, Tuesday, July 26, 2011 at 3:18ame^(-3-x)+22=0

e^(-3-x)=22

ln(e^(-3-x))=ln(22)

-3-x=ln(22)

-x=ln22+3

x=-(ln(22)+3)

x=-6.091

**Related Questions**

Intermediate Algebra - Solve using the substitution method. Show your work. If ...

Algebra - Determine if the function is even, odd or neither. f(x)=2x^5+2x^3 f^-...

algebra - add the following (8.1x^2-5.9x-7.1)+-9.8x^2-8.1x-4.8)

need help in math, - Translate to a system of equations and solve using the ...

ALgebra - I am supposed to preform the indicated divisons: 8x^3-6x^2+2x divided ...

College Algebra - The point (6, 2) lies on the line -x – 8y = -22. Determine if ...

College Algerbra - Solve the inequality. 0.1(0.1x+0.1) _< -0.8

Calculus please help - Use the Midpoint Rule to approximate the integral from 7 ...

college algebra - please solve by method of substitution 0.3x-0.4y-0.33=0 0.1x...

algebra - A charitable fund's balance is modeled by y = -4.1x^2 + 7.1x + 145, ...